ChemInform Abstract: [Bi4]6‐ — The Zintl Anion with the Highest Charge per Atom Obtained from Solution. Issue 16 (22nd April 2014) - Benda, Christina B.; Faessler, Thomas F.
Abstract Dark blue crystals of K6[Bi4](NH3)8 are obtained from a solution of the Zintl phase KBi in liquid NH3 in the presence of 18‐crown‐6 (‐70 °C, 3 months; 20‐30% yield).